A Rapid Spectroscopic Method for the Identification of the Filamentous Fungi Isolated From Turkish Traditional Mold-Ripened Cheeses - Kirtil, Hatice Ebrar; Cebi, Nur; Metin Yildirim, Rusen; Metin, Banu; Arici, Muhammet; Kırtıl, Hatice Ebrar (Elsevier, 2024)
Fourier transform infrared spectroscopy (FTIR) is an alternative microbial identification technique due to its faster analysis times and lower cost compared to molecular methods. In this study, forty-three fungal strains isolated from different Turkish traditional mold-ripened cheeses representing nine different Penicillium species (P. roqueforti, P. corylophilum, P. before, P. crustosum, P. spinulosum, P. rubens, P. brevicompactum, P. paneum, and P. solitum) were analyzed by using FTIR HTS-XT (High Throughput Screening Extension) method in the 4000–400 cm
Keywords: Mold-ripened cheese; Filamentous fungi; Identification; FTIR; Hierarchical clustering analysis (HCA)